2015
DOI: 10.1016/j.metabol.2015.09.005
|View full text |Cite
|
Sign up to set email alerts
|

A prevalent caveolin-1 gene variant is associated with the metabolic syndrome in Caucasians and Hispanics

Abstract: Context and objective We examined whether a prevalent caveolin-1 gene (CAV1) variant, previously related to insulin resistance, is associated with metabolic syndrome (MetS). Patients and methods We included subjects genotyped for the CAV1 variant rs926198 from two cohorts: 735 Caucasians from the HyperPATH multicenter study, and 810 Hispanic participants from the HTN-IR cohort. Results Minor allele carriers from HyperPATH cohort (57% of subjects) had higher Framingham risk scores, higher odds of diabetes (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
48
0
8

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(62 citation statements)
references
References 42 publications
6
48
0
8
Order By: Relevance
“…In a multiple regression model, sodium‐modulated aldosterone suppression‐to‐stimulation index levels were significantly higher in CAV1 minor allele carriers compared with noncarriers, even when adjusted by age, sex, body mass index, and site of study (β=0.06, P =0.04). Moreover, in adjusted logistic regression, minor allele carriers had higher odds of having IR (odds ratio 2.36 [95% CI 1.50–3.69]) and low HDL (odds ratio 1.54 [95% CI 1.01–3.37]), consistent with our previous reports on normal sodium diet . There were no differences by genotype in aldosterone or cortisol (Table ) or in resistin, adiponectin, or 24‐hour urinary sodium (data not shown).…”
Section: Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…In a multiple regression model, sodium‐modulated aldosterone suppression‐to‐stimulation index levels were significantly higher in CAV1 minor allele carriers compared with noncarriers, even when adjusted by age, sex, body mass index, and site of study (β=0.06, P =0.04). Moreover, in adjusted logistic regression, minor allele carriers had higher odds of having IR (odds ratio 2.36 [95% CI 1.50–3.69]) and low HDL (odds ratio 1.54 [95% CI 1.01–3.37]), consistent with our previous reports on normal sodium diet . There were no differences by genotype in aldosterone or cortisol (Table ) or in resistin, adiponectin, or 24‐hour urinary sodium (data not shown).…”
Section: Resultssupporting
confidence: 90%
“…Moreover, in adjusted logistic regression, minor allele carriers had higher odds of having IR (odds ratio 2.36 [95% CI 1.50-3.69]) and low HDL (odds ratio 1.54 [95% CI 1.01-3.37]), consistent with our previous reports on normal sodium diet. 11,12 There were no differences by genotype in aldosterone or cortisol ( Table 2) or in resistin, adiponectin, or 24-hour urinary sodium (data not shown).…”
Section: Clinical and Biochemical Characteristics Categorized By Cav1mentioning
confidence: 89%
See 1 more Smart Citation
“…Unlike the other SNP hits in this study, TBX15 did not differ by gender[139]. Candidate gene studies have shown that CAV1 polymorphisms resulting in decreased expression of the gene are associated with insulin resistance and the metabolic syndrome in Hispanic and Caucasian cohorts[140, 141]. …”
Section: Risk Factors For Af: Hypertension Obesity and Common Genetimentioning
confidence: 76%
“…While the MC2R gene acts on adrenal steroidogenesis and regulation of the glucocorticoid axis, the MC5R gene regulates the function of sebaceous glands with effect on water repulsion and thermoregulation 56 . In turn, the CIB1 gene encodes a protein involved in cell proliferation, particularly proplatelets, therefore acting on thrombopoiesis 57 , while the CAV1 gene has a critical role in signal transduction and trafficking for its interplay with steroid receptors and is associated with the metabolic syndrome in humans 58 .…”
Section: Discussionmentioning
confidence: 99%